A truncated form of the Pho80 cyclin redirects the Pho85 kinase to disrupt vacuole inheritance in S. cerevisiae (The Rockefeller University Press, 1995)
Partitioning of the vacuole during cell division in Saccharomyces cerevisiae begins during early S phase and ends in late G2 phase before the yeast nucleus migrates into the bud neck. We have isolated and characterized a new mutant, vac5-1, which is defective in vacuole segregation. Cells with the vac5-1 mutation can form large buds without vacuoles. The VAC5 gene was cloned and is identical to PHO80. PHO80 encodes a cyclin which acts in a complex with a cdc-like kinase, PHO85, as a negative regulator of two transcription factors (PHO2 and PHO4) that govern the expression of metabolic phosphatases. The vacuole inheritance defect in vac5-1 cells is dependent on the presence of the Pho85 kinase and its targets Pho4p and Pho2p. As with other alleles of PHO80, phosphatase levels are elevated in vac5-1 mutants. A suppressor, the COOH-terminal half of the Gal11 transcription factor, rescues the vac5-1 phenotype of defective vacuole inheritance without altering the vac5-1 phenotype of elevated phosphatase levels. In addition, neither maximal nor minimal levels of expression of the inducible "PHO" system phosphatases causes a vacuole inheritance defect. Though vac5-1 is recessive, pho80 delta or pho85 delta strains do not show a defect in vacuole inheritance, suggesting that vac5-1 is not a complete loss-of- function allele. Sequence analysis shows that the vac5-1 allele encodes a truncated form of the Pho80 cyclin and overexpression of vac5-1 in pho80 delta cells causes a vacuole inheritance defect. We conclude that the vac5-1 allele directs the Pho85 kinase to regulate, via transcription factors Pho4 and Pho2, genes that affect vacuole inheritance but which are not known to be under normal PHO pathway control.